Extraction in the food industry - Shevtsova, Kateryna; Rudnytska, Kateryna (My University, 2022)
The review of methods of extraction and stages which are distinguished in the extraction process in the food industry.
Keywords: кафедра іноземних мов професійного спрямування; екстракт; extract; екстрагування; extraction; харчова промисловість; food industry; екстрагуюча речовина; extracted substance